Kajian Fenomenologi Ritual Nampah Batu Di Pura Puseh Desa Adat Depeha - I Putu Mardika (Pramana: Jurnal Hasil Penelitian, 2021)
This article examines the phenomenology of the Nampah Batu ritual at Puseh Temple, Depeha Traditional Village which is held once a year, precisely when Purwani Purnama Sasih Karo, which is one day before Purnama Sasih Karo. In this ritual, a unique offering is made called ngatarang lelampadan with offerings from the produce of the Depaha Village community after harvest. In addition there is a unique procession called nampah batu, which is a stone symbolized by a pig as a means of ceremony. There are several theories to dissect the problems studied, namely phenomenological theory, functionalism theory and religious theory. This research is a qualitative research with a qualitative approach. The type of data used is qualitative data and is supported by quantitative data. Data sources are primary data sources and secondary data sources. Data were collected using observation, interview, and documentation techniques. From the data collected, it was processed using qualitative descriptive methods through data analysis methods. The results, namely (1) The stages of the Nampah Batu ritual at the Puseh Temple, Pakraman Depeha Village, Kubuaddan District, Buleleng Regency are as follows: the first stage is registration at the Village Temple administratively to be recorded in the Tulud Apuh list; the second stage is the ritual of praying together at Puseh Temple; the third stage is the implementation of the ceremony at Yeh Kedis Temple, the fifth stage is prayer followed by eating together. The functions of the Nampah Batu ritual are: a) manifest functions, namely: 1) social functions 2) aesthetic cultural functions 3) educational functions 4) ethical and cultural functions. Meanwhile b) latent functions are: 1) religious function 2) purification function and 3) symbolic function. The meaning of the nampah stone ritual at Puseh Temple, Depeha Village, Kubutambahan District, Buleleng Regency is etymological meaning and symbolic meaning.